Replacement of the Alpha variant of SARS-CoV-2 by the Delta variant in Lebanon between April and June 2021. Issue 7 (25th July 2022) - Merhi, Georgi; Trotter, Alexander J.; de Oliveira Martins, Leonardo; Koweyes, Jad; Le-Viet, Thanh; Abou Naja, Hala; Al Buaini, Mona; Prosolek, Sophie J.; Alikhan, Nabil-Fareed; Lott, Martin; Tohmeh, Tatiana; Badran, Bassam; et al.
Abstract : The COVID-19 pandemic continues to expand globally, with case numbers rising in many areas of the world, including the Eastern Mediterranean Region. Lebanon experienced its largest wave of COVID-19 infections from January to April 2021. Limited genomic surveillance was undertaken, with just 26 SARS-CoV-2 genomes available for this period, nine of which were from travellers from Lebanon detected by other countries. Additional genome sequencing is thus needed to allow surveillance of variants in circulation. In total, 905 SARS-CoV-2 genomes were sequenced using the ARTIC protocol. The genomes were derived from SARS-CoV-2-positive samples, selected retrospectively from the sentinel COVID-19 surveillance network, to capture diversity of location, sampling time, sex, nationality and age. Although 16 PANGO lineages were circulating in Lebanon in January 2021, by February there were just four, with the Alpha variant accounting for 97 % of samples. In the following 2 months, all samples contained the Alpha variant. However, this had changed dramatically by June and July 2021, when all samples belonged to the Delta variant. This study documents a ten-fold increase in the number of SARS-CoV-2 genomes available from Lebanon. The Alpha variant, first detected in the UK, rapidly swept through Lebanon, causing the country's largest wave to date, which peaked in January 2021. The Alpha variant was introduced to Lebanon multiple times despite travel restrictions, but the source of these introductions remains uncertain. The Delta variant was detected in Gambia in travellers from Lebanon in mid-May, suggesting community transmission in Lebanon several weeks before this variant was detected in the country. Prospective sequencing in June/July 2021 showed that the Delta variant had completely replaced the Alpha variant in under 6 weeks.